The Use of Artificial Intelligence (AI) among International Class Program Students and Its Implication in Their Learning - Handayani, Eka Wahyu; Ramadhani, Qurrota A’yun; Rozan, Akhmad Nur Mahdi; Al ‘Azmi, M. Naufal Tsabit (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
Artificial Intelligence (AI) is a technology that enables computers to mimic human intellectual abilities, such as learning from experience, identifying patterns, making decisions, and completing complex tasks. AI is currently a popular topic in the field of education, where it can assist teachers in tasks like creating lesson plans, assessing learning outcomes, and providing support to students. AI can also benefit learners by improving their academic performance, making learning more interesting and interactive. AI also believed as a tool for mastering several foreign languages. One of the programs at universities that required students to master a single foreign language is International Class Program (ICP). AI could have an impact in improving academic performance of ICP students. By the case, this study aims to explore the use of AI among International Class Program (ICP) students and its implications for their learning. A survey was conducted among 46 ICP students from seven different majors in the Faculty of Tarbiya and Teacher Training, Maulana Malik Ibrahim State Islamic University of Malang. The results showed that AI is mostly used by ICP students for searching for translations, looking for inspiration, and finding answers. The use of AI has implications for ICP students, such as the lack of mastery of foreign languages. However, AI can also help students master foreign languages quickly, easily, and efficiently. AI can also help students do assignments, find ideas, and create designs or discussions. The information provided by AI tends to be more concise, easy to understand, and informative. The advantages of using AI include helping students find answers efficiently, making it easier for students to find additional information, being practical, growing student inspiration, imagination and creativity, helping students develop a better understanding of technology, assisting in developing designs or discussions, and helping translate accurately. The disadvantages of using AI include dependence, making students lazy, providing inaccurate information, eliminating students' critical thinking, reducing students' literacy, and using non-standard language. In conclusion, AI has both advantages and disadvantages in education. While AI can help students learn more efficiently and effectively, it can also make students lazy and dependent on technology. Therefore, it is essential to use AI wisely and not abuse it in education.